A New High-Throughput Analysis for Drug Metabolism Profiling Using Liquid Chromatography Coupled with Tandem Mass Spectrometry - Kusumoto, K.; Nagao, T.; Ogihara, T. (Drug Research, 2013)
We developed 3 liquid chromatography (LC) methods coupled to tandem mass spectrometry for comprehensive high-throughput profiling of drug metabolism, employing different columns with gradient systems of aqueous 10 mmol/L ammonium acetate and acetonitrile. The methods were established using testosterone (TST), imipramine (IMP), acetaminophen (APAP) and salbutamol (SBM), which have markedly different values of partition coefficient, P. Method I, using an octadecylized silica (ODS) column (ACQUITY UPLC BEH C18) with a steep gradient, was suitable for analyzing TST and its metabolites, and IMP and its metabolites. These substrates could not be analyzed by Method II, using another ODS column (Atlantis dC18), or Method III, using an Atlantis HILIC silica column. APAP and its metabolites could be analyzed simultaneously by Method II, but not Method I or III. SBM and its metabolites could be detected simultaneously only by Method III. The developed analytical methods were further evaluated with a panel of 18 additional drugs. Based on the retention times and peak shapes, we propose general criteria, in terms of calculated LogP (cLogP) value, for method selection. Broadly speaking, drugs with high cLogP, those with intermediate cLogP and those with low cLogP were best analyzed by Methods I, II and III, respectively, although drugs with borderline values of cLogP could be evaluated by both the relevant methods. The injection cycle for each method was within 10 min, including up to 3 min conditioning time. These methods are expected be useful in high-throughput screening assays to examine biotransformations of candidate drugs.
Keywords: biotransformation; metabolite; cLogP